Signatures of the Solar Transient Disturbances Over the Low Latitude Ionosphere During 6 to 8 September 2017. Issue 9 (6th September 2018) - Bagiya, Mala S.; Thampi, Smitha V.; Hui, Debrup; Sunil, A. S.; Chakrabarty, D.; Choudhary, R. K.
Abstract: Low latitude ionospheric behavior during solar transient disturbances of solar flares and storm time penetrating electric fields comprises an important part of the Earth's space weather. The flares enhance the electron density of the sunlit ionosphere by supplying excess solar radiation. However, the degree of these density changes is subjective if a geomagnetic storm persists simultaneously. The present case study addresses the ionospheric variations over the Indian longitudes under the combined effects of the solar flares and a geomagnetic storm during 6 to 8 September 2017 and probably the first of its kind in delineating the effects of these two over the low latitude ionosphere. The X9.3 class flare of 6 September, which occurred during non‐storm conditions, produced an intense E region ionization ( 500% over the ambient). However, the total electron content response to this flare was comparatively weak. The flares on 7 and 8 September occurred during the 7–8 September geomagnetic storm. Though the 8 September flare occurred with higher intensity (M8.1) and early in local time compared to the flare of 7 September (M7.3), the equatorial electrojet current enhancement was lesser on 8 September ( 75% over the ambient) than that of 7 September ( 110% over the ambient). This aspect is discussed in view of the storm time convection effects over the low latitudes during 7–8 September storm. The total electron content did not respond to the flares of 7 and 8 September. This behavior is attributed to the varying center‐to‐limb distance of the solar active region 12673 during this period. Key Points: This study delineates the effects of flare and storm time electric fields over the low‐latitude ionosphere during 6 to 8 September 2017 The role of center‐to‐limb distance of active region 12673 in changing E and F ‐region densities during X9.3 flare on 6 September is assessed Storm time PPE field and composition changes caused significant low‐latitude TEC enhancements, while the similar was absent at the equator